Versus III : Beeldende kunst theater muziek. - Eeckout, Tanguy; Matthynssens, Pieter; Oudenaarde (Oudenaarde : KunstadStroom, 2005)
Berenhaut, Marianne ; Catrysse, Wim ; Cole, Stijn ; Delrue, Ronny ; Leroy, Annik ; Lybeer, charlotte ; Michiels, Mike ; Nollet, Lieven ; Oosterlynck, Sabine ; Timmermans, Ante ; Vandaele, Kim ; Vandenberg, Philippe ; et al.
Oudenaarde, 16 september - 30 oktober 2005
Programmatie theater-muziek-beeldende kunst
kunstcatalogus